First report of Crimean-Congo hemorrhagic fever virus exposure in human and livestock populations, Center Region, Cameroon - Gasparine, Morena; Namekong Fokeng, Armand; Lopez, Eva; Mvodo, Stephanie; Thirion, Laurence; Paguem, Archile; Charrel, Remi; de Lamballerie, Xavier; Falchi, Alessandra (Frontiers in Cellular and Infection Microbiology, 2025)
Crimean-Congo hemorrhagic fever (CCHF) is a widespread, tick-borne viral infection present in many African countries. Its epidemiology and impact on public health remain poorly understood in Cameroon. The main objective of the current study was to investigate the circulation of CCHF virus (CCHFV) in ruminants (cattle and goats), humans, and ticks collected simultaneously in a study area of Akonolinga, a health district in the central region of Cameroon. From the 15 to 28 July 2024, a cross-sectional study was conducted in Akonolinga, by collecting survey data and serum samples (from humans, goats, and cattle) and picking ticks from cattle and goats. This study included 100 randomly selected households from eight localities. Data were also collected using questionnaires to assess CCHFV seropositivity-associated factors. Individual characteristics of 189 goats and 246 cattle were collected and the data geo-referenced. To assess the prevalence of CCHF, serological enzyme-linked immunosorbent assay (ELISA) and molecular (real-time Reverse Transcriptase (RT) PCR) methods were used to detect antibodies targeting CCHF viral nucleoprotein and CCHFV-specific RNA in collected sera, respectively. The presence of CCHFV-specific RNA was also assessed in tick homogenate using real-time RT PCR. The overall CCHFV seroprevalence was 1.9% [95% CI (1.02%–3.64%)] in humans, 10.9% [n = 42; 95% CI (8.15%–14.38%)] in cattle, and 3.38% [n = 5; 95% CI (1.45%–7.66%)] in goats. Seroprevalence in cattle increased significantly with age. A total of 554 ticks were collected from 162 of the 386 (42%) cattle examined, with Rhipicephalus (Boophilus) microplus being the dominant species. CCHFV RNA was detected in two sera of women sampled. Phylogenetic analysis of a small portion of the L segment classified the strain within the African genotype III. This study reported, for the first time, the proven exposure of the human population to CCHFV in central Cameroon, showing strong evidence that CCHFV is infecting humans. Serological analyses revealed exposure of cattle and goats to CCHFV-strains collected in the same geographical area. These results demonstrate the potential risk of CCHF emergence in the human population, especially in rural areas in close vicinity with animals.